Purification, crystallization and preliminary crystallographic study of a recombinant plant aminoaldehyde dehydrogenase from Pisum sativum - Tylichová, Martina; Briozzo, Pierre; Kopečný, David; Ferrero, Julien; Morera, Solange; Joly, Nathalie; Snegaroff, Jacques; Šebela, Marek (Acta crystallographica. Section F, 2008)
Aminoaldehydes are products of polyamine degradation and are known to be reactive metabolites that are toxic to living cells at high concentrations. These compounds are catabolized by aminoaldehyde dehydrogenases, which are enzymes that contain a nicotinamide adenine dinucleotide coenzyme. Aminoaldehyde dehydrogenase from Pisum sativum was overexpressed in Escherichia coli, purified and crystallized using the hanging-drop method. A complete data set was collected to 2.8 A resolution at 100 K. Crystals belong to the monoclinic space group P2(1), with unit-cell parameters a = 86.4, b = 216.6, c = 205.4 A, beta = 98.1 degrees. Molecular replacement was performed and led to the identification of six dimers per asymmetric unit.
Keywords: Aldehyde Dehydrogenase; Recombinant Proteins; Crystallization; western blotting; Spectrometry, Mass, Matrix-Assisted Laser Desorption-Ionization; Base Sequence; Cloning, Molecular; krystalizace; Financing, Organized; Crystallography, X-Ray; Protein Conformation; sekvence nukleotidů; konformace proteinů; klonování DNA; financování organizované; rekombinantní proteiny; DNA Primers; spektrometrie hmotnostní - ionizace laserem za účasti matrice; DNA primery; hrách setý; Pisum sativum; elektroforéza v polyakrylamidovém gelu; Electrophoresis, Polyacrylamide Gel; aldehyddehydrogenasa; Blotting, Western; krystalografie rentgenová